2009
DOI: 10.1159/000214212
|View full text |Cite
|
Sign up to set email alerts
|

The Search for a New Marker of Renal Function in Older Patients with Chronic Kidney Disease Stages 3–4: Usefulness of Cystatin C-Based Equations

Abstract: Background/Aim: Cystatin C (Cys C) is an endogenous marker of glomerular filtration rate (GFR) unaffected by body composition. The aim of the present study was to assess the utility of Cys C-based GFR prediction equations (Hoek, Larsson and Stevens) and creatinine (modification of diet in renal disease-isotope dilution mass spectrometry – MDRD-IDMS, and Cockcroft-Gault – CG) compared with 51Cr-EDTA. Methods: This study was carried out in 40 Caucasian older patients with advanced age (≥60) and chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Another study carried out in Sweden [9] showed an improvement in the accuracy of eGFR when calculated lean mass was included in the prediction equation. None of these studies have employed the CKD-EPI equation and are limited to relatively small groups of patients or special populations [5,6,7,8,9,10,11,12]. Our study suggests that body composition may also be of importance in the general population but the effect may be of lesser magnitude than in these selected populations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Another study carried out in Sweden [9] showed an improvement in the accuracy of eGFR when calculated lean mass was included in the prediction equation. None of these studies have employed the CKD-EPI equation and are limited to relatively small groups of patients or special populations [5,6,7,8,9,10,11,12]. Our study suggests that body composition may also be of importance in the general population but the effect may be of lesser magnitude than in these selected populations.…”
Section: Discussionmentioning
confidence: 78%
“…Several previously published studies on the relationship between muscle mass and measured GFR suggest that lean mass might influence eGFR when calculated using the MDRD equation [5,6,7,8,9,10,11,12]. For example, Macdonald et al [10] found that in non-diabetic CKD patients appendicular lean mass index explained an additional 10% of the variability in measured GFR after adjusting for creatinine, age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cystatin C was introduced as a good marker of early renal function decline [19,20], particularly in diabetic [21] or elderly [22] patients. Cystatin C is being considered as a potential replacement for serum creatinine because it appears to be less affected by muscle mass [23], and most studies have shown that it is more highly correlated with GFR than is serum creatinine [20,24].…”
Section: Introductionmentioning
confidence: 99%